How to Design Hydrogen Storage Materials? Fundamentals, Synthesis, and Storage Tanks. (26th June 2019) - Lai, Qiwen; Sun, Yahui; Wang, Ting; Modi, Poojan; Cazorla, Claudio; Demirci, Umit B.; Ares Fernandez, Jose Ramon; Leardini, Fabrice; Aguey‐Zinsou, Kondo‐François
Abstract: As the world shifts toward renewable energy, the need for an effective energy carrier is pressing. Hydrogen has often been touted as a universal clean energy vector and the fuel of the future. Unfortunately, mass adoption of the hydrogen economy is slow due to a lack of incentives and technical difficulties in storing hydrogen. Better materials capable of reversible hydrogen uptake/release with hydrogen capacity surpassing 5 mass% at the ambient must emerge. So far, finding such materials has been elusive; alloys capable of ambient hydrogen uptake/release have a low storage capacity while high capacity hydrides have a very high hydrogen release temperature. From metal alloys to complex hydrides, a better understanding of the behavior of hydrogen in hydrides is essential to fine‐tune their properties toward application. Herein, the latest approaches to design hydrogen storage materials based on known hydrides are reviewed with the aim to facilitate the emergence of alternative thinking toward the design of better hydrogen storage materials. Synthetic methods and conceptual approaches to achieve particular hydrogen thermodynamics and kinetics are discussed. These include metallurgical alloying, mechanochemical modification, chemical destabilization, the nanosizing approach, and theoretical modeling and machine learning techniques to guide experimental work. Abstract : The "art" of material design for hydrogen storage relies on mastering divergent requirements. This review aims to summarize recent strategies to design better hydride materials toward the storage and use of hydrogen as a clean energy carrier.